2020
DOI: 10.2147/ijwh.s268169
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Novel Risk-Scoring Model for Prediction of Premalignant and Malignant Lesions of Uterine Endometrium Among Symptomatic Premenopausal Women</p>

Abstract: Purpose Uterine cancer is the second most prevalent cancer of the female genital tract, with 90% of it being of endometrial origin. The aim of this research was to create and validate a risk-scoring model using patients’ clinical variables in predicting premalignant and malignant lesions of the uterine endometrium among premenopausal women with abnormal uterine bleeding (AUB). Methods This is a retrospective cohort study conducted at a tertiary hospital of Southern Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…EH/EEC is the cause of AUB in 5%–14% of AUB patients [ 18 ]. Bagepalli Srinivas et al [ 19 ] retrospectively analyzed the clinical data of 472 women with AUB (including 20 with AH and 8 with EEC) who were aged ≤ 55 years and established a predictive scoring model for AH/EC in symptomatic premenopausal women. This model included the variables of age ≥ 45 years (1 point), anovulatory bleeding (3 points), combined diabetes (3 points), and BMI ≥ 30 kg/m 2 (2 points).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EH/EEC is the cause of AUB in 5%–14% of AUB patients [ 18 ]. Bagepalli Srinivas et al [ 19 ] retrospectively analyzed the clinical data of 472 women with AUB (including 20 with AH and 8 with EEC) who were aged ≤ 55 years and established a predictive scoring model for AH/EC in symptomatic premenopausal women. This model included the variables of age ≥ 45 years (1 point), anovulatory bleeding (3 points), combined diabetes (3 points), and BMI ≥ 30 kg/m 2 (2 points).…”
Section: Discussionmentioning
confidence: 99%
“…The final included indicators were metabolic diseases, family history, age ≥ 40 years, ultrasonic blood flow RI ≤ 0.5, and ET ≥ 10 mm, and the AUC value of the model was 0.837. The study population of Bagepalli [ 19 ], Jha [ 20 ], Giannella [ 18 ], Ruan [ 25 ], and Tingthanatikul [ 23 ] was AUB patients. Our study targeted young women (age < 40 years), patients with endometrial abnormalities, as suggested by AUB or TVUS, were studied, and therefore, the results have a wider range of clinical applicability.…”
Section: Discussionmentioning
confidence: 99%